WOMEN’S COSTUME OF THE EAST GERMAN TRADITION WITH BIG TWO-PLATE BROOCHES IN THE CIMMERIAN BOSPORUS AND NORTH CAUCASUS IN THE GREAT MIGRATION PERIOD - Mastykova, Anna Vladimirovna; Kazanskij, Mihail Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article examines the women's costume of the East German tradition, widespread in the North Caucasus and Crimea during the Great Migration Period. It is characterized by one or two big two-plate brooches (more than 10 cm long), worn on the chest or shoulders. In Crimea and Taman, a costume with such brooches in the first half of the 5th century had a prestigious character. In the Caucasus, most of the burials with this costume were found on the Black Sea coast of the North Caucasus, primarily at the Durso burial ground near modern Novorossiysk. In the VI century, written sources record the Gothic Tetraxites here. In the Vth century, the Tetraxite Goths moved from Eastern Crimea to the North Caucasus. Outside the coastal zone, large double-plate brooches and their smaller copies are found on sites of the Pashkovsky - Karpovka type, which belonged to the proto-Adyghe population of the Kuban and Black Sea region. A costume with two double-plate brooches was certainly considered prestigious, at least among the Tetraxite Goths who left the Durso necropolis. The graves in which the outfit in question was located usually had quite rich grave goods. The costume with double-plate brooches on the chest and shoulders was of East German origin. Its prototype existed in the Chernyakhov archaeological culture. During the Hunnic period, a costume with small two-plate brooches, which became especially widespread in the Chernyakhov culture and in the northern Black Sea region, where it became the basis for the formation of a “princely” costume with big brooches of a similar shape. In turn, in the second half of the Vth century, this prestigious costume became the prototype of a headdress with large double-plate brooches as a “folk” copy of the prestigious costume of the Hunnic period. This costume became typical of the “middle class” among the East Germans and became widespread in the Barbaricum from the North Caucasus to the Pyrenees.